The relation between subjective well‐being and career aspirations amongst a sample of adolescents in low socioeconomic status communities in Cape Town. Issue 8 (16th September 2020) - Manuel, Donnay; Savahl, Shazly; Casas, Ferran; Tiliouine, Habib; Isobell, Deborah; Mpilo, Mulalo; Florence, Maria; Adams, Sabirah
Abstract: The study aimed to determine the relation between adolescents' subjective well‐being and career aspirations. The study further aimed to determine the extent to which social support mediates this relation. The sample comprised 1082 adolescents in Grades 8–11, selected from schools located in low socioeconomic status communities in Cape Town, South Africa. The overall model demonstrated a nonsignificant relation between adolescents' subjective well‐being and career aspirations. Across gender, the results indicated a significant relation between subjective well‐being and career aspirations for the male group, but not for females. The results further indicate that social support did not mediate the relation between adolescents' subjective well‐being and career aspirations for the pooled sample. However, for females, the study found a significant negative relation between social support and aspirations. We recommend targeting interventions at an institutional level, inclusive of challenging gender roles and providing information about educational and career opportunities for young people.